2013
DOI: 10.1021/jo401594r
|View full text |Cite
|
Sign up to set email alerts
|

Molecular “Pincer” from a Diimidazolium Salt: A Study of Binding Ability

Abstract: The anion recognition ability of the dicationic imidazolium salt 3,3'-di-n-octyl-1,1'-(1,3-phenylenedimethylene)diimidazolium 1,5-naphthalenedisulfonate ([m-Xyl-(oim)2][1,5-NDS]) was investigated in acetonitrile solution by means of proton NMR titrations. A wide range of anions, comprising simple inorganic ions, halides, and mono- and dicarboxylates was taken into account. The study showed that this receptor binds carboxylate anions more strongly than halides. Moreover [m-Xyl-(oim)2][1,5-NDS] displays selectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 56 publications
0
10
0
Order By: Relevance
“…We have recently investigated the anion recognition ability of 3,3′‐di‐ n ‐octyl‐1,1′‐(1,3‐dimethylenebenzene)diimidazolium 19 (R = C 8 H 17 ; A = 1,3‐Ar) [1,5‐NDS 2– ] in acetonitrile by means of 1 H NMR titrations 69. Several anions ([H 2 PO 4 – ], [NO 3 – ], acetate, pyruvate, lactate, benzoate, 2‐methylpropanoate, oxalate, succinate, fumarate, tartrate, malonate, [Cl – ], [Br – ], and [I – ]) were examined.…”
Section: Applicationsmentioning
confidence: 99%
“…We have recently investigated the anion recognition ability of 3,3′‐di‐ n ‐octyl‐1,1′‐(1,3‐dimethylenebenzene)diimidazolium 19 (R = C 8 H 17 ; A = 1,3‐Ar) [1,5‐NDS 2– ] in acetonitrile by means of 1 H NMR titrations 69. Several anions ([H 2 PO 4 – ], [NO 3 – ], acetate, pyruvate, lactate, benzoate, 2‐methylpropanoate, oxalate, succinate, fumarate, tartrate, malonate, [Cl – ], [Br – ], and [I – ]) were examined.…”
Section: Applicationsmentioning
confidence: 99%
“…[17] Notably,t he nature of the spacer interposed between the charged heads can introduce af urtherd egree of control on their behavior. In this context, in the last years we have studied the properties of dicationic imidazolium salts bearing as ymmetrically substituted aromatic spacer.B yi ntroducing subtle structural changes,s uch as by varying the alkyl chain length, the nature of the anion, andt he substitution pattern of the spacer, we have been able to obtain more organized reaction media, [18] selectiveh osts for anion recognition, [19] and low molecular weight gelators. [20] Moreover,c ombining p stacking with the highly directional nature of hydrogen bonds may serve as af urther tool to tune the spatiala rrangement of the monomersc onstituting the aggregates.…”
Section: Introductionmentioning
confidence: 99%
“…Noto et al reported dipod 36 for determination of halide and carboxylate anions through 1 H NMR studies. Probe 36 showed significant downfield shift of imidazolium C‐2H proton upon addition of various anions, which revealed the participation of ImC2‐H in binding.…”
Section: Recognition Of Halides and Acetatementioning
confidence: 99%